National Economy in the Conditions of the Globalization and Market Internationalization: Competition and Innovations Potential - Melnikas, Borisas (Ekonomika, 2002)
The main problems and priorities of the preparing and realization of the long - term national innovation strategies in Lithuania and other East - and Central European countries are exposed. The priorities of national innovation strategies in the context of general trends of the development of national economies in the conditions of the globalization and market internationalization processes are described. Definitions of the national economy system and of the national economy as the subject of the economic activities in the international and global market are discuss. The phenomenons of globalization. international integration and information societies development as the main factors of the modernization of national economies in the Eastern - and Central Europe, especially in Lithuania, are described. The possibilities and opportunities of the development of systems and networks of innovation centres, business incubators, science and technology parks, regional - and investment development agencies and other institutions are analyzed: development of the systems and networks of innovation institutions is very important condition of the national economy modernization. Some aspects of the innovations activities in the education, science and university studies system are discuss. Innovations activities as the main factor of the competition in the global market are indicated.